ANALISIS PENGENDALIAN KUALITAS PENGANTONGAN PUPUK NPK PHONSKA DENGAN MENGGUNAKAN STATISTICAL PROCESSING CONTROL (SPC) PADA PENGANTONGAN 02/03 PRODUKSI II A PT. PETROKIMIA GRESIK - elan, umi; Farabi, Achmad Rizal (Fakultas Ekonomi Universitas Gresik, 2018)
This study aims to analyze whether the quality control of NPKPhonska fertilizer feeding at bagging 02/03 production II A PT.Petrokimia Gresik is controlled or not controlled as well as finding thecauses of product defects in the company. In this study the method ofanalysis is using Statistical Process Control, which is a process used tomonitor standards, making measurement and taking corrective actionwhile a product or service is being produced. Informants in this studyamounted to 13 people. Data retrieval techniques use observation,interviews and documentation. The results of this study indicate that thequality control NPK Phonska fertilizer feeding at bagging 02/03production II A PT. Petrokimia Gresik is still not under control, withdefect of 1,17% in 15 days. Type most defect that frequently happen is thebag broke as much 3.860 pcs with a percentage of 48,92%. While theweight of the scales is not appropriate as much 3.158 pcs with apercentage of 40,03% and for bag leak as much 872 pcs with apercentage of 11,05%. From the results of field observation andinterviews, the factors that cause this defect is human, machine,environtment, work method, and raw materials.ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â DOI : 10.5281/zenodo.3475660